2021
DOI: 10.1063/5.0068659
|View full text |Cite
|
Sign up to set email alerts
|

RHEED analysis of the oxidized M′2M″xXyene sheets by ablated plasma thrust method in pulsed laser deposition chamber

Abstract: M′2M″xXyene (M′ and M″ are the early transitional metals and X is carbide with x = 1 for y = 2 and x = 2 for y = 3) are the ordered double transitional metal layered carbides derived from their parent MAX phases M′2M″xAlXyene by a wet chemical etching method. Their oxides are predicted to have topological properties for which they should be annealed at around 800 °C in an oxygen background. This paper includes the new ablated plasma thrust method for the ionization and adsorption of oxygen on the M′2M″xXyene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The Scherer's Formula is, 𝐷 = 𝑘𝜆 𝛽𝑐𝑜𝑠𝜃 where, D = crystallites size (nm) for k = 0.9 (Scherer's constant), λ=0.15406 nm (wavelength of the x-ray sources), β=FWHM (radians) and 𝜃 = Peak position (radians). The peak position and FWHM are determined from XRD data [13,[29][30][31][32][33][34][35][36].…”
Section: Crystallites Size From Scherer's Equationmentioning
confidence: 99%
“…The Scherer's Formula is, 𝐷 = 𝑘𝜆 𝛽𝑐𝑜𝑠𝜃 where, D = crystallites size (nm) for k = 0.9 (Scherer's constant), λ=0.15406 nm (wavelength of the x-ray sources), β=FWHM (radians) and 𝜃 = Peak position (radians). The peak position and FWHM are determined from XRD data [13,[29][30][31][32][33][34][35][36].…”
Section: Crystallites Size From Scherer's Equationmentioning
confidence: 99%
“…Yongsheng Chen and others successfully fabricated PVC/Fe2O3 ultrafiltration membranes with excellent performance, potentially expanding their use in nanofiltration processes [24]. Our recent works on ferrites and MXenes [25] show their efficiency in the energy [1] conversion devices. These developments underscore the versatility and utility of PVC-based membranes in a wide range of applications, owing to their favorable mechanical and chemical properties.…”
Section: Introduction Rechargeable Batteries and Polymer Electrolyte ...mentioning
confidence: 86%
“…Zhang et al (2021) evaluated the inflammatory response of MXene-polymer nanocomposites in vitro and in vivo. The study demonstrated low levels of inflammatory cytokine production and minimal tissue inflammation upon exposure to MXene-polymer nanocomposites, highlighting their biocompatibility and suitability for biomedical applications (Zhang, Y., Wang, S., Liu, X., & Chen, 2021).…”
Section: Inflammatory Responsementioning
confidence: 99%
“…From few years back, we have studied the MXenes and Ferrites ( Parajuli, Raghavendra, et al, 2021 ; Parajuli, Murali, Rao, Ramakrishna, et al, 2022 ; Parajuli, Taddesse, Murali, and Samatha 2022 ; Parajuli, Murali, Raghavendra, et al, 2023 ; Parajuli, Murali, Samatha, et al, 2023 ) separately and their mixtures with the most exploited material in the society polymer in the form of their nanocomposites ( Parajuli et al, 2022 ; Parajuli, Uppugalla, et al, 2023 ). We found them most efficient combination among the recently developed other nanocomposites which are far efficient than their pristine form.…”
Section: Mxene Polymer and Their Nanocompositesmentioning
confidence: 99%